2009
DOI: 10.1128/jcm.01363-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ST9 Methicillin-Resistant Staphylococcus aureus among Pigs and Pig Handlers in Malaysia

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) of sequence type 398 (ST398) has frequently been detected in pigs and pig handlers. However, in Malaysia, sampling 360 pigs and 90 pig handlers from 30 farms identified novel ST9-spa type t4358-staphylococcal cassette chromosome mec type V MRSA strains that were found to transiently colonize more than 1% of pigs and 5.5% of pig handlers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 21 publications
(15 reference statements)
6
84
5
1
Order By: Relevance
“…The prevalence of CC9, the most prevalent MRSA lineage among pigs, varies widely: 1.4 % in Malaysia [135], 10 % in Thailand [136], 4 to 13.9 % in Taiwan [137,138], 11.4 to 14.7 % in China [139,140], and 21.3 % in Hong Kong [141]. However, a recent study found a high nasal rate (40 %) of MRSA CC9 among pigs in Thailand [142].…”
Section: Evolution Of La-mrsa In Asiamentioning
confidence: 87%
See 3 more Smart Citations
“…The prevalence of CC9, the most prevalent MRSA lineage among pigs, varies widely: 1.4 % in Malaysia [135], 10 % in Thailand [136], 4 to 13.9 % in Taiwan [137,138], 11.4 to 14.7 % in China [139,140], and 21.3 % in Hong Kong [141]. However, a recent study found a high nasal rate (40 %) of MRSA CC9 among pigs in Thailand [142].…”
Section: Evolution Of La-mrsa In Asiamentioning
confidence: 87%
“…MRSA CC9 isolates also have been detected in dust samples from pig farms in China [143] and at a low frequency in chickens and meat (chicken and beef) samples from Hong Kong [141,144]. Similarly, MRSA CC9 among pig farmers in Asian countries also appears low (5-19 %) [135,138,139].…”
Section: Evolution Of La-mrsa In Asiamentioning
confidence: 88%
See 2 more Smart Citations
“…However, the epidemiology of LA-MRSA difers in other geographic areas. A diferent strain of LA-MRSA, CC9, appears to be the prominent type in several Asian countries [28][29][30][31][32]. Poultry may harbor CC398 strains [16,33,34] but CC5 [33,35] and other types unrelated to CC398 have also been reported [36].…”
Section: Introductionmentioning
confidence: 99%